EFFECT OF PROBLEM POSING METHOD (PPM) TOWARD VERBAL CREATIVITY JUNIOR HIGH SCHOOL STUDENTS IN GRADE 7th - Bagus Priambodo; Anita Listiara; Tri Puji Astuti (Jurnal EMPATI, 2018)
Verbal creativity is the ability to think fluence, flexible, and original that manifested through the words. A child who has good verbal creativity will be easier to carry out activities in school and in the surrounding environment. Psychological freedom is onefactor that can develop creativity. One alternative teaching methods that provide freedom in an atmosphere of learning is the Problem Posing Method (PPM) which is triggered by Paulo Freire. This research aims to determine the presence or absence of the influence of PPM on verbal creativity in junior high school students in grade 7th. Characteristics of the subjects of this study were junior high school students in grade 7th, received conventional learning materials, and have never had learning by using PPM. This study uses a non-randomized pretest-posttest control group design. Subjects in the study were divided into two groups in nonrandomized, based on available classes. The selection of these two classes based on the homogeneity of the two classes in terms of teacher, the way teachers teach, subject matter, and the mid term exam. Subjects in the experimental group 33 students, while subjects in the control group 35 people. The data was collected using the Verbal Creativity Test The results of hypothesis testing is done using the Independent Sample T Test techniques produce differences in the mean value of 3.294 with significance value less than alpha level, which is equal to 0.014 (a= 0.05). The results showed that there are significant differences in students' verbal creativity scores of the experimental group who received treatment Problem Posing Method (PPM) with a control group who did not receive treatment.